PERSEPSI MASYARAKAT TERHADAP PEMILAHAN SAMPAH (Studi Masyarakat Jakarta, Tangerang, Bekasi, Depok) - Widodo, Lestario (BPPT)
Act No. 18 of 2008 on Waste Management mandate that the community or household is the beginning of the stage of waste management processes, which make waste separation. Up to know solid waste management in urban area is still a complex problem, either from social, management, or technology aspects. The other problem of solid waste management is due to the people behaviour, which is mostly still unaware. Community respondents do not wish to waste segregation and argued that the waste separation should be done by the government. Seen thatthe awareness for change in how to manage the waste is still low. Local governments still need to continue to disseminate the Act No. 18 of 2008 on Waste Management and provide motivation to the community or households that are willing to segregation waste at the source.Keywords : waste, waste separation, community perception of waste